Ages of Mankind. (2nd October 2019) - Wesley, Deborah
Abstract : As we move through life in the world, the quality of our participation changes. Initially, as newborns, we are not even aware of a difference between ourselves and everything, everyone else. In the small domestic world ("home"), we experience parental care and accept being taught how to behave, how to be. This process continues into school years and the adjustments that allow life with our peers. Ultimately, in adolescence there is felt a beginning need for independence of action and feeling. With adulthood, making a life in the bigger world requires the force of will against obstacles and for goals. At midlife, there comes another gradual shift to the question of meaning in life and of old age and death. All these changes reflect a procession of ways in which the ego or consciousness relates to inner and outer worlds.